FLUID INVOLVEMENT IN NORMAL FAULTING - Sibson R.H. (My University, 2000)
Evidence of fluid interaction with normal faults comes from their varied role as flow barriers or conduits in hydrocarbon basins and as hosting structures for hydrothermal mineralisation, and from fault-rock assemblages in exhumed footwalls of steep active normal faults and metamorphic core complexes. These last suggest involvement of predominantly aqueous fluids over a broad depth range, with implications for fault shear resistance and the mechanics of normal fault reactivation. A general downwards progression in fault rock assemblages (high-level breccia-gouge (often clay-rich) -> cataclasites -> phyllonites -> mylonite -> mylonitic gneiss with the onset of greenschist phyllonites occurring near the base of the seismogenic crust) is inferred for normal fault zones developed in quartzo-feldspathic continental crust. Fluid inclusion studies in hydrothermal veining from some footwall assemblages suggest a transition from hydrostatic to suprahydrostatic fluid pressures over the depth range 3-5 km, with some evidence for near-lithostatic to hydrostatic pressure cycling towards the base of the seismogenic zone in the phyllonitic assemblages. Development of fault-fracture meshes through mixed-mode brittle failure in rock-masses with strong competence layering is promoted by low effective stress in the absence of thoroughgoing cohesionless faults that are favourably oriented for reactivation. Meshes may develop around normal faults in the near-surface under hydrostatic fluid pressures to depths determined by rock tensile strength, and at greater depths in overpressured portions of normal fault zones and at stress heterogeneities, especially dilational jogs. Overpressures localised within developing normal fault zones also determine the extent to which they may reutilise existing discontinuities (for example, low-angle thrust faults). Brittle failure mode plots demonstrate that reactivation of existing low-angle faults under vertical σ1 trajectories is only likely if fluid overpressures are localised within the fault zone and the surrounding rock retains significant tensile strength. Migrating pore fluids interact both statically and dynamically with normal faults. Static effects include consideration of the relative permeability of the faults with respect to the country rock, and juxtaposition effects which determine whether a fault is transmissive to flow or acts as an impermeable barrier. Strong directional permeability is expected in the subhorizontal σ2 direction parallel to intersections between minor faults, extension fractures, and stylolites. Three dynamic mechanisms tied to the seismic stress cycle may contribute to fluid redistribution: (i) cycling of mean stress coupled to shear stress, sometimes leading to postfailure expulsion of fluid from vertical fractures; (ii) suction pump action at dilational fault jogs; and, (iii) fault-valve action when a normal fault transects a seal capping either uniformly overpressured crust or overpressures localised to the immediate vicinity of the fault zone at depth. The combination of σ2 directional permeability with fluid redistribution from mean stress cycling may lead to hydraulic communication along strike, contributing to the protracted earthquake sequences that characterise normal fault systems.